Sozialraum - Kessl, Fabian; Landhäußer, Sandra; Ziegler, Holger (Aktivierende Sozialpädagogik. Ein kritisches Glossar)
"Aktivierung" ist zum zentralen Leitbild der Transformation der westlichen Wohlfahrtsstaaten geworden - wenngleich sich abzeichnet, dass die Bilanzen der Politiken der "Aktivierung" eher vernichtend ausfallen. Aus sozialpädagogischer Perspektive enthält der aktuelle - vorrangig ökonomisch orientierte - sozialpolitische Aktivierungsdiskurs vielfältige Optionen, in denen genuin pädagogische Interventionsformen nur undeutlich definiert werden. Das Glossar greift derzeit zentrale Begriffe auf und positioniert und hinterfragt wichtige Referenzen sozialpädagogischer Aktivierung in ihren Kernaussagen. In der Aufarbeitung der sozialpädagogischen Qualität der einzelnen Begriffe wird offensichtlich, dass sie in der Verwendung im politischen Diskurs nicht deckungsgleich sind.
Keywords: Beratung Bildung Bürgergesellschaft Case Management Dienstleistung Erlebnisorientierung Lebenswelt Lebensweltorientierung Qualitätsmangement Sozialpädagogik Sozialraum Zivilgesellschaft

Social Capital - Landhäußer, Sandra; Ziegler, Holger (Social Work & Society)
In the broadest sense social capital reflects the idea of resources rooting in relations between individuals resp. in the embeddings of people in groups, associations, communities and even societies. A central assumption is that social capital - as a resource - is emerging from the quality of these relationships. This quality may be described in a more materialistic sense because these relations open up access to specific resources or assets. But it may also be imbued with valuated connotations, in particular referring to the essential contribution of networks and trust in promoting well-being, a sense of belonging and decency as individuals in entities blessed with social capital are pretended to engage in mutually beneficial collective actions. Therefore social capital applies to peoples’ shared expectations, norms, values, and beliefs, their commitments to each other and eventually their associative capacities to knit the ‘social fabric’.
Keywords: Social Capital

How can multimodal cues from child-directed interaction reduce learning complexity in robots? - Rohlfing, Katharina; Fritsch, Jannik; Wrede, Britta; Jungmann, Tanja (Advanced Robotics)

Facilitating the acquisition of UNDER by means of IN and ON - a training study in Polish - Rohlfing, Katharina (Journal of Child Language)
Forty Polish children aged between 1;8 and 2;3 were trained over two training sessions In the comprehension of the preposition POD [UNDER]. In the experiment, two variables were manipulated: a within Subjects variable of SITUATION and a between subjects variable of LINGUISTIC INPUT. The effect of situation could be found in all trained groups, showing that children's understanding in familiar and transfer Situations differed significantly from the performance of the control group in the post-test. The results further Suggest that depending on the type of a situation, the linguistic task requires different word learning abilities from a child.

How can multimodal cues from child-directed interaction reduce learning complexity in robots? - Rohlfing, Katharina; Fritsch, Jannik; Wrede, Britta; Jungmann, Tanja (Advanced Robotics)
Robots have to deal with an enormous amount of sensory stimuli. One solution in making sense of them is to enable a robot system to actively search for cues that help structuring the information. Studies with infants reveal that parents support the learning-process by modifying their interaction style, dependent on their child's developmental age. In our study, in which parents demonstrated everyday actions to their preverbal children (8-11 months old), our aim was to identify objective parameters for multimodal action modification. Our results reveal two action parameters being modified in adult-child interaction: roundness and pace. Furthermore, we found that language has the power to help children structuring actions sequences by synchrony and emphasis. These insights are discussed with respect to the built-in attention architecture of a socially interactive robot, which enables it to understand demonstrated actions. Our algorithmic approach towards automatically detecting the task structure in child-designed input demonstrates the potential impact of insights from developmental learning on robotics. The presented findings pave the way to automatically detect when to imitate in a demonstration
Keywords: multi-modal motherese; child-directed input; motionese; learning mechanisms

How to make sense of environmental interaction and dynamics. Symposium: Models of infant development: Are we really serious about environmental interaction and dynamics? - Wrede, Britta; Rohlfing, Katharina; Nagai, Yukie (5th Biennial International Conference on Infant Studies (ICIS 2006))

Comparison of multimodal annotation tools: Workshop report - Rohlfing, Katharina; Loehr, D.; Duncan, S.; Brown, A.; Franklin, A.; Kimbara, I.; Milde, J.-T.; Parrill, F.; Rose, T.; Schmidt, T.; Sloetjes, H.; Thies, A.; et al. (Gesprächsforschung)

Factors influencing feedback - Muhl, Claudia; Wrede, Britta; Rohlfing, Katharina (Proceedings of the Workshop on How people talk to computers, robots, and other artificial communication partners)

„Ich bin gespickt mit tausend Messern“. Zeit- und Streitgedichte. - Topalović, Elvira

Let’s not rock the boat. Frauenorganisationen und Demokratisierung in Malaysia - Spiegel, Anna; Dannecker, Petra (Internationales Asienforum)

mWatch Salzburg. A Survey on Mobile Readiness in the City of Salzburg and its Regional Context - Fuchs, Christian; Haselmayer, Sascha; Maier-Rabler, Ursula

Grundeinkommen – In Freiheit tätig sein (Guaranteed Basic Income – Activity in Freedom)

Towards a Global Sustainable Information Society (GSIS)? - Fuchs, Christian (tripleC)

The Self-Organization of Virtual Communities - Fuchs, Christian (Journal of New Communications Research)

The Self-Organization of Social Movements - Fuchs, Christian (Systemic Practice and Action Research)

Informatik und Gesellschaft: Ein notwendiger Zusammenhang (Informatics and society: a necessary connection) - Fuchs, Christian; Hofkirchner, Wolfgang (Technik- und Wissenschaftssoziologie in Österreich: Stand und Perspektiven (Sociology of science and technology in Austria: State of the art and perspectives). Sonderband der Österreichischen Zeitschrift für Soziologie)

Wissenskapitalismus und bedingungsloses Grundeinkommen (Knowledge capitalism and guaranteed basic income) - Fuchs, Christian (Grundeinkommen – In Freiheit tätig sein (Guaranteed basic income – activity in freedom))

Cyberprotest und Demokratie (Cyberprotest and democracy) - Fuchs, Christian (Digitale Medien – neue Möglichkeiten für Demokratie und Partizipation? (Digital media: new opportunities for democracy and participation?)

The Self-organization of Cyberprotest - Fuchs, Christian (The Internet Society II: Advances in Education, Commerce & Governance)

The Nature-Society-System and the Global Sustainable Information Society - Fuchs, Christian (Cybernetics and Systems 2006, Volume 2)

Sustainability and the Information Society - Fuchs, Christian (Social Informatics: An Information Society for all? In Remembrance of Rob King. Proceedings of the 7th International Conference “Human Choice and Computers', IFIP-TC9 'Relationship between Computers and Society“)

Fuschl Extension: Igniting a New Form of Conversation - Fuchs, Christian; Horiuchi, Yoshihide; Kordes, Urban; Rivera, Barbara; Rowland, Gordon; Walton, Doug (Proceedings of the Thirteenth Fuschl Conversation)

Information Society – Sustainable or Not? - Fuchs, Christian (Sustainable Solutions for the Information Society. Proceedings of 11th International Conference on Urban Planning and Spatial Development in the Information Society)

Co-operative Cyberethics for a Sustainable Information Society - Bichler, Robert; Fuchs, Christian; Raffl, Celina (International Sociological Association: Proceedings of the XVI World Congress of Sociology. The Quality of Social Existence in a Globalising World. CD-ROM)

Kleine Chance für Subjekte? - Matzner, Tobias (Simulation Next, Munitionsfabrik Nr. 17 (2006))

Postmoderne Mythophorie in "Die Entdeckung der Currywurst" - Müller, Inez (Zur Darstellung von Zeitgeschichte in deutschsprachiger Gegenwartsliteratur)

The Dialectic of the Nature-Society-System - Fuchs, Christian (tripleC)

Wie nachhaltig ist die Informationsgesellschaft? (How sustainable is the information society?) - Fuchs, Christian (Stadtanalyse)

Broadening eParticipation: Rethinking ICTs and Participation. ICT&S Research Paper No. 2 - Fuchs, Christian; Bernhaupt, Regina; Kramer, Mark A.; Maier-Rabler, Ursula

eParticipation research: A Case Study on Political Online Debate in Austria. ICT&S Research Paper No. 1 - Fuchs, Christian

Ökonomien des Medialen. Tausch, Wert und Zirkulation in den Medien- und Kulturwissenschaften

Schwarm oder Masse? Mechanismen der Selbststrukturierung der Medienrezeption - Adelmann, Ralf (Ökonomien des Medialen. Tausch, Wert und Zirkulation in den Medien- und Kulturwissenschaften)

"Zu schön, um wahr zu sein". Bildkritik der Medien - Adelmann, Ralf (Kulturindustrie reviewed. Ansätze zur kritischen Reflexion der Mediengesellschaft)

Ökonomien des Medialen oder: Kunden, die dieses Buch gekauft haben, haben auch folgende Einleitung gelesen - Adelmann, Ralf (Ökonomien des Medialen. Tausch, Wert und Zirkulation in den Medien- und Kulturwissenschaften)

Friedensethik als Aufgabe für Ausbildung und Qualifizierung in der Kirche. Eine Annäherung in fünf Thesen - Freitag, Christine (epd Dokumentation 25/2006)

Vermittlung – Eine zentrale, aber vernachlässigte Kategorie professionellen Handelns in der internationalen Zusammenarbeit - Freitag, Christine

PLAZ-Entwicklungsstrategie – Professional School für Bildungsforschung und Lehrerbildung - Herzig, Bardo; Hilligus, A. H.; Langenbacher-Liebgott, J.; Reinhold, P.; Rinkens, H.-D. (PLAZ-Forum – Lehrerausbildung und Schule in der Diskussion, Heft 14)

Sind die Neuen Medien in der Schule angekommen? - Herzig, Bardo (Schulen ans Netz (Hrsg.): Themendienst Nr. 4 –Dezember 2006.)

Der Medieneinsatz an Freien Lernorten - Grafe, S.; Herzig, Bardo (Handreichung Freie Lernorte – Raum für mehr)

„Musterprozesse“ in der Medienentwicklung. Eine interdisziplinäre Sichtweise - Herzig, Bardo (ForschungsForum Paderborn 01/2007)

Zukunftsfähiges Lernen an freien Lernorten - Herzig, Bardo; Grafe, S. (Freie Lernorte – Raum für mehr.)

Außergewöhnliche Geschichten von normaler Mediennutzung - Bartz, Christina (transcriptionen)

Kulturschutt. Über das Recycling von Theorien und Kulturen

Museumskonzeptionen und Geschichtskultur im 19. Jahrhundert - Hartung, Olaf (Museum und Geschichtskultur. Ästhetik – Politik – Wissenschaft)

Museum und Geschichtskultur. Ästhetik – Politik – Wissenschaft

Mit Telemann durch die deutsche Fernsehgeschichte. Kommentare und Glossen des Fernsehkritikers Martin Morlock

Zu: Clas Dammann: Stimmen aus dem Äther – Fenster zur Welt. Die Anfänge von Radio und Fernsehen in Deutschland. Köln 2005 - Bartz, Christina (H-Soz-U-Kult 2 (09.05.06))

Museum, Archiv, Netz. Popgeschichte(n) als Mediengeschichte(n) - Jacke, Christoph (Testcard. Beiträge zur Popgeschichte)

Die Kritikindustrie: Wir sind Paps und wollen keinen - Jacke, Christoph (Testcard. Beiträge zur Popgeschichte)

Popmusik als Seismograph. Über den Nutzen wissenschaftlicher Beobachtung von Pop - Jacke, Christoph (Kulturschutt. Über das Recycling von Theorien und Kulturen)